American clown [videorecording (DVD)] - Reilly, John C., 1965-; Arquette, David; Irwin, Bill, 1950- (Vision Films, 2026)
Clowns have been a symbol of humor and laughter since they first donned the iconic red nose and oversized shoes. Those who devote their lives to the craft spend years perfecting it. From circuses to birthday parties to movies, clowns are everywhere in our culture, but what happens the laughter fades and the greasepaint runs? One man sets out to find what's left of America's once beloved clown.